Carrie - King, Stephen, 1947- (Pocket Books, 1999)
A modern classic, Carrie introduced a distinctive new voice in American fiction -- Stephen King. The story of misunderstood high school girl Carrie White, her extraordinary telekinetic powers, and her violent rampage of revenge, remains one of the most barrier-breaking and shocking novels of all time. Make a date with terror and live the nightmare that is - Carrie.